Frameworks and cases on evolutional supply chain - Higuchi, Toru (Advances in logistics, operations, and management science (ALOMS) book series., 2022)
"This book gives readers the frameworks of evolutional supply chain through symbolic case studies helping more people understand the dynamic aspects of the supply chain, such as changes in the suppliers, factory and storage locations, production processes, distribution structures and more"--